Effect of Urinary Protein C Inhibitor on Lipopolysaccharide-induced Disseminated Intravascular Coagulation in Rats - Fujita, Mitsugu; Izutani, Wakako; Komurasaki, Yoshikazu (Thrombosis and Haemostasis, 2000)
The effect of urinary protein C inhibitor (uPCI) on disseminated intravascular coagulation (DIC) was investigated using an experimental DIC in rats. uPCI (0.5 and 1.0 mg/kg) was continuously administrated into the left femoral vein of the rats with lipopolysaccharide (50 mg/kg)-induced DIC. In all doses, uPCI significantly prevented the drastic changes in the parameters such as fibrinogen concentration, activated partial thromboplastin time (APTT), prothrombin time (PT), fibrin/fibrinogen degradation products (FDP) level, aspartate aminotransferase (AST) level and alanine aminotransferase (ALT) level. Furthermore, uPCI significantly inhibited the increase in the levels of plasma kallikrein and thrombin which act not only as the procoagulant proteases but also as the chemotactic factors to neutrophils and monocytes. These results show that uPCI may prevent hypercoagulation, the induction of secondary fibrinolysis and organ failure in the DIC model. Therefore, uPCI may be a useful agent for the clinical treatment of DIC.
Keywords: Urinary protein C inhibitor; DIC; experimental DIC in rat